2022
DOI: 10.1097/hco.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

How to deal with nonsevere stenoses in coronary artery bypass grafting – a critical perspective on competitive flow and surgical precision

Abstract: Purpose of reviewFor invasive treatment of coronary artery disease (CAD), we assess anatomical complexity, analyse surgical risk and make heart-team decisions for percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG). With PCI, treating flow-relevant lesions is recommended, and reintervention easily treats disease progression. For CABG, some stenoses may only be borderline or nonsevere despite a clear surgical indication. As reoperations are not easy, the question on how to address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…To complete this confusion, Urso et al 26 presented the best long-term outcomes with bilateral internal thoracic artery grafting compared with left internal thoracic artery plus radial artery, but the differences only appeared after 10 years. We reviewed various factors influencing patency of grafts 27 and suggested that surgical precision and experience taking all factors into account may influence patency rates more than only one factor (such as graft type, degree of competitive flow, or target vessel quality; ►Fig. 2B).…”
Section: Surgical Treatment Of Coronary Artery Diseasementioning
confidence: 99%
“…To complete this confusion, Urso et al 26 presented the best long-term outcomes with bilateral internal thoracic artery grafting compared with left internal thoracic artery plus radial artery, but the differences only appeared after 10 years. We reviewed various factors influencing patency of grafts 27 and suggested that surgical precision and experience taking all factors into account may influence patency rates more than only one factor (such as graft type, degree of competitive flow, or target vessel quality; ►Fig. 2B).…”
Section: Surgical Treatment Of Coronary Artery Diseasementioning
confidence: 99%